Disasters in the United States : Frequency, Costs, and Compensation - Brusentsev, Vera; Vroman, Wayne (Book collections on Project MUSE., 2017)
The authors examine examine the increasing frequency of disasters in the United States along with their costs, compensation, mitigation strategies, and where different types are likely to occur.